PELATIHAN PUBLIC SPEAKING: FIRST IMPRESSION STARTS WITH WORDS - Ismamudi; Hamzah Muhammad Mardi Putra; Nani Hartati; Ahmad Gunawan (Jurnal Pengabdian Pelitabangsa, 2023)
Public Speaking Training: First Impression Starts with Words is a community service activity that aims to improve the verbal and non-verbal communication skills of student organization members in creating a good first impression through words. In the context of student organization leadership, effective public speaking skills are essential to influence, motivate, and lead organization members towards a common goal. This training was conducted using workshop methods, practical exercises, and evaluation sessions. The training participants were members of student organizations from various backgrounds, including core officers, active members, and prospective officers. They had an interest in developing their communication skills and wanted to learn how to make a positive first impression through their words. The outcomes of the training included an increase in participants' public speaking skills and confidence. Participants also experienced an increase in their understanding of the importance of positive first impressions in influencing audiences and building good relationships with organizational members. The training had a positive impact in improving participants' communication skills in the context of student organization leadership.